Modern greek grammar notes for absolute beginners A user-friendly grammar for levels A1/A2 - Πουλοπούλου, Μαρία; Σταμούλη, Σπυριδούλα (Αθήνα : Σύνδεσμος Ελληνικών Ακαδημαϊκών Βιβλιοθηκών, 2015)
This book aims at providing a comprehensive account of elementary Modern Greek for learners with little or no previous knowledge of the language. The concept of grammar implied in this context extends far beyond the theoretical description per se to include practical guidance towards effective communication, as well as commentary of cultural and linguistic relevance. The grammar is presented from an absolute beginner’s point of view, prioritizing what is more basic in language learning, with a consistent focus on use, meaning, and pronunciation. Grammar points are explained in an everyday style that echoes teaching in class, with the minimum of relevant terminology. They are combined with numerous examples (along with their oral version) in order to familiarize students with the use of the language. The book is structured in 11 Chapters (with exercises for further practice), an Appendix, a Glossary, and its translation in Modern Greek.
Keywords: Greek language -- Grammar; Grammar modern greek case gender tense aspect; Linguistics -- Fields of linguistics -- Fieldw related to the structure of language -- Grammar; Linguistics -- Fields of linguistics -- Applied linguistics -- (Human) language instruction; Linguistics -- Fields of linguistics -- Applied linguistics; Linguistics -- Fields of linguistics -- Applied linguistics -- (Human) language instruction -- Foreign language instruction